2001
DOI: 10.1128/jb.183.16.4823-4838.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence and Comparative Analysis of the Solvent-Producing BacteriumClostridium acetobutylicum

Abstract: The genome sequence of the solvent-producing bacterium Clostridium acetobutylicum ATCC 824 has been determined by the shotgun approach. The genome consists of a 3.94-Mb chromosome and a 192-kb megaplasmid that contains the majority of genes responsible for solvent production. Comparison of C. acetobutylicum to Bacillus subtilis reveals significant local conservation of gene order, which has not been seen in comparisons of other genomes with similar, or, in some cases closer, phylogenetic proximity. This conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
599
2
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 735 publications
(620 citation statements)
references
References 88 publications
8
599
2
6
Order By: Relevance
“…However, in contrast, (i) methanogenic nif gene promoters are typical archaeal promoters, and the transcriptional apparatus is similar to that of Eucarya (Langer and Zillig 1993, Marsh et al 1994, Langer et al 1995, Qureshi et al 1995, Hausner et al 1996, Thomm 2000, Bell and Jackson 2001, (ii) the archaeal nif genes are present in a single operon, and (iii) all diazotrophic methanogens contain two open reading frames (ORFs) inserted between nifH and nifD that show a strong similarity to glnB (Sibold et al 1991, Merrick and Edwards 1995, Arcondeguy et al 2001, Kessler et al 2001. Recently, this nif gene organization with the two glnB-like genes, which have been renamed nifI 1 and nifI 2 (Arcondeguy et al 2001), has also been found in Clostridium acetobutylicum (Nölling et al 2001) and Clostridium beijerinckii (Chen et al 2001). The presence of the nifI ORFs within the bacterial nif operon may be the result of a horizontal interdomain gene transfer, or this respective arrangement is ancestral and other bacteria have lost it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast, (i) methanogenic nif gene promoters are typical archaeal promoters, and the transcriptional apparatus is similar to that of Eucarya (Langer and Zillig 1993, Marsh et al 1994, Langer et al 1995, Qureshi et al 1995, Hausner et al 1996, Thomm 2000, Bell and Jackson 2001, (ii) the archaeal nif genes are present in a single operon, and (iii) all diazotrophic methanogens contain two open reading frames (ORFs) inserted between nifH and nifD that show a strong similarity to glnB (Sibold et al 1991, Merrick and Edwards 1995, Arcondeguy et al 2001, Kessler et al 2001. Recently, this nif gene organization with the two glnB-like genes, which have been renamed nifI 1 and nifI 2 (Arcondeguy et al 2001), has also been found in Clostridium acetobutylicum (Nölling et al 2001) and Clostridium beijerinckii (Chen et al 2001). The presence of the nifI ORFs within the bacterial nif operon may be the result of a horizontal interdomain gene transfer, or this respective arrangement is ancestral and other bacteria have lost it.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was recently found that the nif cluster of C. acetobutylicum shows the same gene organization, as two nifI genes are located between nifH and nifD (Nölling et al 2001). These findings suggest that the nitrogenase subunits of the Methanosarcina species are more closely related to the clostridial nitrogenases than to the archaeal nitrogenases of Methanococcus and Methanothermobacter.…”
Section: Sequencing and Nucleotide Analysis Of The Nif Gene Cluster Fmentioning
confidence: 99%
“…There a re comprehensive descriptions concerning autolysins in Bacillus subtilis (Smith et al, 2000), which is moderately related to C. acetobutylicum (Nolling et al, 2001), thus providing a theoretical reference for our research. In B. subtilis 168, eight genes representing conserved elements of four autolysin families (Table 1) were extracted from Kyoto Encyclopedia of Genes and Genomes (KEGG, http://www.genome.jp/kegg/).…”
Section: Identifi Cation Of Putative Autolysin Genes In C Acetobutylmentioning
confidence: 99%
“…Microbial ecology and functional diversity of natural habitats F Rubino et al phosphate pathway to the histidine biosynthesis pathway (Nölling et al, 2001) was also significantly more diverse in Clostridium than Prevotella (Po0.01, average of 2.76 versus 0.13). This supports reports that species of Clostridium may utilise histidine as part of a strategy to overcome nutrient limitation during the stationary growth phase (Fonknechten et al, 2010).…”
Section: Metabolic Adaptations In Clostridiummentioning
confidence: 99%